Assessment of Sensory Attributes in White Tea Utilizing the High Identity Traits (HITS) Methodology Employing an Immersive Approach - Rinaldi, Ahmad; Hunaefi, Dase; Adawiyah, Dede Robiatul; Sholehuddin, Zen Fauzan; Dwinawati, Elisabeth; Zeller, Yves Henri Marie (Jurnal Teknologi dan Industri Pangan, 2024)
White tea is a plant-derived product from Camellia sinensis L, which is processed without enzymatic oxidation and fermentation. The high identity traits (HITS) is a sensory evaluation method that identifies dominant attributes using five attributes to describe each sample. The sensory evaluation research on white tea uses the HITS method with an environmental approach aimed at identifying dominant attributes of white tea using both trained and untrained panelists, as well as at determining the intensity of these dominant attributes using an environmental approach with both trained and untrained panelists. The materials used were five samples of Gamboeng white tea, Heizl, Dandang, Pucuk, and Ennie1. The HITS method with trained panelists successfully identified dominant attributes as follows: yellow-brown brew color, rose aroma, rose flavor, astringent aftertaste, and light mouthfeel. Meanwhile, the experiment using untrained panelists showed dominant attributes as follows: yellow-brown brew color, jasmine aroma, jasmine flavor, astringent aftertaste, and light mouthfeel. The HITS method with an immersive approach for both trained and untrained panelists had an impact on increasing the intensity of aroma, flavor, and mouthfeel while decreasing the intensity of aftertaste.